Development of Smart Box Learning Media on the Material of the Human Respiratory System - Donna Rhamdan; Dominggus Dominggus (Unversitas Muhammadiyah Mataram, 2025)
The type of research carried out in this study is research and development (R&D). This research aims to develop Smart Box learning media that is validated by media expert validators, material experts, linguists, and practitioners. This research also aims to find out the attractiveness of Smart Box learning media. This research and development process uses the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The validation results resulted in 100% of media experts, 94% of material experts, 84% of linguists, and 97.1% of practitioners, all of whom were categorized as very deserving. The results of validation from media, material, language, and practitioner experts show that Smart Box learning media is very feasible to be used in the learning process. The results of the limited trial were 92.9%, while the field trial yielded 88.8%, both of which were categorized as very interesting. The results of the student response questionnaire conducted during the limited trial and field trial showed that students were very interested in the Smart Box learning media.